Clinicopathological Staging of Dynamics of Neurodegeneration and Neuronal Loss in Alzheimer Disease. Issue 1 (3rd December 2020) - Wegiel, Jerzy; Flory, Michael; Kuchna, Izabela; Nowicki, Krzysztof; Ma, Shuang Yong; Wegiel, Jarek; Badmaev, Eulalia; Leon, Mony de; Wisniewski, Thomas; Reisberg, Barry
Abstract: Clinical and neuropathological staging of Alzheimer disease (AD) neurodegeneration and neuronal loss dynamics is the baseline for identification of treatment targets and timing. The aim of this study of 14 brain regions in 25 subjects diagnosed with AD and 13 age-matched control subjects was to establish the pattern of neurodegeneration, and the severity and rate of neuronal loss in mild cognitive impairment/mild AD (Functional Assessment Staging [FAST] test 3–4), moderate to moderately severe AD (FAST 5–6), and severe AD (FAST 7). The study revealed (1 ) the most severe neuronal loss in FAST 3–4; (2 ) the highest rate of neuronal loss in FAST 5–6, to the "critical" point limiting further increase in neuronal loss; (3 ) progression of neurofibrillary degeneration, but decline of neuronal loss to a floor level in FAST 7; and (4 ) structure-specific rate of neuronal loss caused by neurofibrillary degeneration and a large pool of neuronal loss caused by other mechanisms. This study defines a range and speed of progression of AD pathology and functional decline that might potentially be prevented by the arrest of neuronal loss, both related and unrelated to neurofibrillary degeneration, during the 9-year duration of mild cognitive impairment/mild AD.